Outcomes of diaphyseal femoral fractures treatment in relation to fracture union and full weight bearing among adults - Muhammad Atif; Muhammad Abdul Basit; Muhammad Zaman Khan; Muhammad Ali Usman; Syed Shaharyar Shah; Amlouk Ijaz (Journal of University Medical & Dental College, 2022)
BACKGROUND & OBJECTIVE: The femoral shaft fractures constitute 50% of all femoral fractures. The objective is to observe the outcome of diaphyseal femur fracture treatment of femur shaft with the union and full weight bearing by bridge plate osteosynthesis among adults. METHODOLOGY: A Prospective observational study was conducted in the department of Orthopaedic Surgery, Postgraduate Medical Institute/Lahore General Hospital. A sample of 30 patients was calculated using WHO calculator. Convenient sampling was used for patient selection. After reducing the fracture (indirectly), the other end of the plate was also fixed with screws. Data was collected at 6th months post-operatively to see radiological union and weight-bearing status. Data analysis was done using SPSS version 25. Fisher exact test was applied. p-value≤0.05 was considered significant. RESULTS: Mean age of the patients was 34.66±9.22 years. Gender distribution of patients shows that 17% of the patients were females, and 83% of the patients were male. At the 6th month follow-up, all 30 (100%) patients had achieved bony union. At the 5th month, 14(46.7%) of the operated cases were allowed to bear 36-45 Kg weight (p=0.024), and in the 6th month, there were 20(66.7%) operated cases were allowed to bear full weight after the radiological union (p=0.013). CONCLUSION: Bridge plating technique is a safe, easy, and effective method of fixation for comminuted diaphyseal fractures of long bones in terms of bony union and weight bearing. It has a high rate of union with fewer complications.